Depression, the Mood Disease - Mondimore, Francis Mark, 1953- (Book collections on Project MUSE., 2006)
Dr. Francis Mark Mondimore, author of the best-selling book Bipolar Disorder: A Guide for Patients and Families, here explains depression - its causes and symptoms, and its treatment. He discusses depression in all age groups and in both sexes, as well as bipolar disorder, seasonal affective disorders, and depression that accompanies illness. This edition encompasses more than a decade of new research, advances in pharmacology, and changes in public perception.